2021
DOI: 10.1155/2021/4944570
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intraoperative Frozen Section in the Surgical Management of Patients with Nonmelanoma Skin Cancer

Abstract: Background. Intraoperative frozen section (IFS) is often utilised in the surgical treatment of nonmelanocytic skin cancer (NMSC) in sensitive facial regions when Mohs micrographic surgery (MMS) is not available. Objective. To compare the outcome of NMSC patients with excision performed with and without IFS. Materials and Methods. A retrospective, single-centre study was performed on all patients who had undergone resection of NMSC with and without IFS control at the National University Hospital (NUH) from 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the case of DPA, intraoperative frozen sections may be used to verify negative margins [ 12 ], but ultimately permanent resection is a more accurate method of histopathological analysis. Although data on the use of frozen sections in DPA is scarce, a study showed that using intraoperative frozen sections (IFS) during nonmelanoma skin cancer resection led to a higher complete excision rate compared to cases without the use of IFS [ 13 ]. The rate of complete excision with IFS was 87.2%, which significantly decreased the need for additional surgeries and adjuvant therapies [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of DPA, intraoperative frozen sections may be used to verify negative margins [ 12 ], but ultimately permanent resection is a more accurate method of histopathological analysis. Although data on the use of frozen sections in DPA is scarce, a study showed that using intraoperative frozen sections (IFS) during nonmelanoma skin cancer resection led to a higher complete excision rate compared to cases without the use of IFS [ 13 ]. The rate of complete excision with IFS was 87.2%, which significantly decreased the need for additional surgeries and adjuvant therapies [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…For primary well-demarcated BCCs smaller than 2 cm, in the low-risk group, 3 mm gives satisfactory results. Whereas, in the high-risk group, and for lesions larger than 2 cm, a 4–6 mm margin is suggested for getting clear margins [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The face is the site most affected by BCC, and after the surgical resection, an ideal facial reconstruction must provide functionality and an appropriate cosmetic appearance. Combining a local and an advancement flap can be further done to achieve this goal [ 9 ]. Reconstruction of our patient used a combination of the paramedian forehead flap, developed by Sushruta Samita in ancient India.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 On the other hand, pathology analysis of frozen sections is commonly used but they require on average 20 minutes, which can limit the frequency of their use during a procedure. 3,4 Failing to locate and completely remove tumours often result in follow-up repeat surgery from disease recurrence with concomitant negative impact on patient outcomes.…”
Section: Introductionmentioning
confidence: 99%